Validasi Model Transfer Pengetahuan Dari Perguruan Tinggi Ke Industri Kecil - Indriartiningtias, Retno (Jurnal Teknik Industri, 2011)
Previous research was built the effectiveness of knowledge transfer model from University to Small Industries. The model was validated by enterviews with expert from Trunojoyo University and the owner of Small Industry in Bangkalan. This research is validating the previous ones quantitatively by using questioner. Validated was done in Trunojoyo UniversityÂ and Small Industry in Bangkalan. This research used 22 processes transfered. Based on unit analisys there were two kind of respondents : (1) 22 lecturers as resource of transfer knowledge, (2) 4 small industries as receiver of transfer knowledge. Data was calculated using SEM basedÂ PLS. From the calculated the most factors that affect the effectiveness of knowledge transfer from University to Small Industries are direction of knowledge transfer, availability of receiver, form of knowledge, information system and personal relationship. There are relationship between endogenous variable as previous model. Only one relationship that not significant was relationship between environment characteristic and receiver characteristic.